Case Study : Effectiveness of Foot Massage in Reducing Fall Risk in the Elderly - Hendri Tamara Yuda; Windi Amalia Safitri (Prosiding University Research Colloquium, 2022)
One of the physical declines that occur in the elderly is musculoskeletal due to reducedmuscle mass. As a result of the physical decline, it was finding that the physicalproblems often experienced by the elderly on a daily basis such as the risk of falling. Therisk of falling occurs due to weakening of the muscles in the elderly. Fall prevention isone of the important things in the elderly who are at risk of falling. Fall preventionmeasures are generally more directed at preventing environmental factors that canencourage falls. Various interventions to improve balance and reduce the risk of falls inthe elderly have been developing through several studies, including foot exercises, footmassage and joint range of motion exercises. A case study to describe the results ofnursing care for the risk of falling in the elderly in Singosari Village, Ambal District.This case study uses a descriptive method. The data were obtaining from the results ofinterview observations, physical examinations, and study documentation. Subjectsconsisted of 3 elderly people with nursing problems at the risk of falling. After 5 days ofnursing care, all three patients showed a decreased risk of falling with a decreased TUGTest score. Foot massage is effective in reducing the risk of falls in the elderly.